Describing and mapping of the main existing structures and systematic initiatives and academic activities for surveillance in the EU for zoonoses (transboundary, emerging and re‐emerging) in domestic animals and wildlife. Issue 12 (21st December 2022) - ,; Ferroglio, Ezio; Gavier‐Widen, Dolores; Vada, Catarina Gonçalves Rachele; Zanet, Stefania; Smith, Graham; Gethöffer, Friederike; Keuling, Oliver; Staubach, Christoph; Carola, Sauter‐Louis; Blanco, JA; Podgorski, Tomasz; et al.
Abstract: The present report describes and maps the main existing structures and systematic initiatives and academic activities for surveillance in the EU for transboundary, emerging and re‐emerging zoonoses in domestic animals, wildlife, and the environment, developed by the different sectors, namely human, domestic animal, wildlife and environmental, under One Health approach. This is essential to provide scientific and technical advice and improve future schemes of surveillance. A questionnaire was compiled by MSs and the information collected was complemented by literature reviews about (i) the main existing structures and systematic initiatives or activities, and (ii) academic activities for surveillance in the EU for zoonoses in domestic animals and wildlife. We focused on a 50 zoonotic diseases that were pre‐selected for the prioritisation exercise by the One Health working group of EFSA. In total, 21 countries returned the questionnaire. The analysis of zoonotic disease surveillance evidenced that high fragmentation of surveillance programmes occurs in Europe and therefore the main challenge to integrate One Health surveillance is to integrate different surveillance programmes and One Health sectors to progress towards multi‐host and multi‐sector surveillance programmes. When different sectors oversee the coordination of surveillance programmes, the subsequent integration over the different phases of surveillance is enhanced. A structured approach is needed to determine priorities for surveillance and the approach to be used in European surveillance schemes to achieve a higher benefit‐cost ratio with existing or reduced resources. The literature review indicated potential relevance of the hunting sector to participate in surveillance programmes and a bias towards research in vector‐borne pathogens and vectors by the academia; experience that can be used to build One health surveillance. Recommendations are provided for further implementation of One health surveillance.